2009
DOI: 10.3390/rs1040934
|View full text |Cite
|
Sign up to set email alerts
|

LiDAR Utility for Natural Resource Managers

Abstract: Applications of LiDAR remote sensing are exploding, while moving from the research to the operational realm. Increasingly, natural resource managers are recognizing the tremendous utility of LiDAR-derived information to make improved decisions. This review provides a cross-section of studies, many recent, that demonstrate the relevance of LiDAR across a suite of terrestrial natural resource disciplines including forestry, fire and fuels, ecology, wildlife, geology, geomorphology, and surface hydrology. We anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(81 citation statements)
references
References 115 publications
0
80
0
1
Order By: Relevance
“…Hudak et al (2009) reviewed LiDAR applications for natural resource management [38]. With increasing amounts and improved data quality, acquired simultaneously, LiCHy expands these possibilities.…”
Section: Potential Forest Applications Of Data From Lichy Systemmentioning
confidence: 99%
“…Hudak et al (2009) reviewed LiDAR applications for natural resource management [38]. With increasing amounts and improved data quality, acquired simultaneously, LiCHy expands these possibilities.…”
Section: Potential Forest Applications Of Data From Lichy Systemmentioning
confidence: 99%
“…As such, the existing Landsat TCC uncertainty estimates may be regarded as preliminary with regard to biome-specific studies. Now, with increasing coverage worldwide, high-resolution spaceborne imagery (HRSI) as well as LiDAR samples offer additional and often superior means of reference data collection [38][39][40][41]. Tree cover is estimated from HRSI by visual analysis [33] or by semi-automated object-oriented methods [1,[42][43][44].…”
Section: Assessing Spaceborne Maps Of Tree Cover Across the Ttementioning
confidence: 99%
“…One of the first attempts to use airborne lidar for vegetation mapping was reported by the Canadian Forestry Service, which demonstrated the applicability of profiling airborne lidar for the estimation of height and density of the forest canopy and the ground elevation underneath [1]. This and numerous subsequent studies showed that lidar measurements of vegetation canopy can be used to characterize vegetation vertical structure and derive various physical attributes used for academic research, environmental studies and natural resources management programs [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%